Wewenang Kepala Desa dalam Membina Ketentraman dan Ketertiban Masyarakat Desa di Desa Bodae dan Desa Keliha Kecamatan Sabu Timur Kabupaten Sabu Raijua - Inda Juita Kaho; Saryono Yohanes; Hernimus Ratu Udju (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study was to determine the authority of the village head in fostering community peace and order in the village and to determine and examine the inhibiting factors of the village head's authority in fostering community peace and order in Bodae village and Keliha village. This research uses an empirical juridical approach method, namely the methods and procedures used to solve problems, this research first examines secondary data, then proceeds to conduct research on primary data in the field. The results of the research The authority of the Village Head in fostering the peace and order of the village community has not been carried out effectively, this is because there are several things behind it, namely the theft cases that occur because the environmental security system is not implemented effectively, unguarded livestock such as oxen that enter the residents' garden yards to cause losses to the farming community, chicken gambling can disturb the order of the village community. The inhibiting factors of the authority of the village head are the low level of human resources, the ineffective implementation of the environmental security system, the lack of understanding of the community in understanding order in the village environment.